Synthesis, Antimicrobial Evaluation, and Molecular Modeling Studies of New Thiosemicarbazide‐Triazole Hybrid Derivatives of (S)‐Naproxen. Issue 4 (15th March 2022) - Han, M. İhsan; Ince, Ufuk; Gündüz, Miyase Gözde; Küçükgüzel, Ş. Güniz
Abstract: The discovery of new antimicrobial molecules is crucial for combating drug‐resistant bacterial and fungal infections that pose a dangerous threat to human health. In the current research, we applied a molecular hybridization approach to synthesize original thiosemicarbazide‐triazole derivatives starting from ( S )‐naproxen (7a –7k ). After structural characterization using FT‐IR, 1 H‐NMR, 13 C‐NMR, and HR‐MS, the obtained compounds were screened for their antimicrobial activities against Staphylococcus aureus ATCC 29213, Escherichia coli ATCC 25922, Candida albicans ATCC 10231 and their isolates, as well. Although all compounds were found to be moderate antimicrobial agents, in general, their antibacterial activities were better than antifungal effects. Among the tested compounds, 7j carrying nitrophenyl group on the thiosemicarbazide functionality represented the best MIC value against S. aureus isolate. Finally, molecular docking studies were performed in the active pocket of S. aureus flavohemoglobin to rationalize the obtained biological data. Abstract :